2014
DOI: 10.1111/odi.12244
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the prostaglandin pathway genes and risk of head and neck cancer

Abstract: Genetic variations in prostaglandin pathway genes are associated with risk of HNC and may modify the relationship between use of betel quid or cigarette and development of HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The main product of this enzyme is PGI2, which is the major metabolite of AA and a potent vasodilator and platelet aggregation inhibitor [14]. Although studies of PTGIS are still few, it is known that PTGIS may play an important role in tumorigenesis and cancer development in colon cancer, lung cancer, breast cancer, and head and neck cancer [17,18,34,35]. In addition, PGI2, as a product of PTGIS, has a proinflammatory effect that increases microvascular permeability and an anti-inflammatory effect that stimulates T cell IL-10 production [36].…”
Section: Discussionmentioning
confidence: 99%
“…The main product of this enzyme is PGI2, which is the major metabolite of AA and a potent vasodilator and platelet aggregation inhibitor [14]. Although studies of PTGIS are still few, it is known that PTGIS may play an important role in tumorigenesis and cancer development in colon cancer, lung cancer, breast cancer, and head and neck cancer [17,18,34,35]. In addition, PGI2, as a product of PTGIS, has a proinflammatory effect that increases microvascular permeability and an anti-inflammatory effect that stimulates T cell IL-10 production [36].…”
Section: Discussionmentioning
confidence: 99%
“…Chiang et al found that the AA genotype was significantly associated with OSCC when compared to the GG genotype and had a 1.55-fold increased risk of OSCC [107]. However, two studies found no association between different COX-2-1195G>A polymorphisms and head and neck cancer risk [106,109].…”
Section: Cox-2-1195g>amentioning
confidence: 99%
“…In this GSEA, we found that PTGIS was not enriched at the high expression site as expected, but there were two enrichment peaks, respectively, at the high expression site and the low expression site. This may be due to the different roles of the gene in different diseases; many scholars have found its different roles in different diseases [28][29][30][31][32][33][34][35]. PTGIS plays a positive role in cardiovascular diseases by regulating fatty acid metabolism [29,33,35,36], while it is the opposite in cancer [25,[37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%